Case Report: The Role of Molecular Analysis of the MUTYH Gene in Asymptomatic Individuals - Fabišíková, Katarína; Hamidová, Olívia; Behulová, Regína Lohajová; Závodná, Katarína; Priščáková, Petra; Repiská, Vanda (Frontiers in Genetics, 2020)
MUTYH-associated polyposis (MAP) is a rare hereditary condition caused by the biallelic mutation in MUTYH gene encoding MUTYH glycosylase. This enzyme is a key member of the base excision repair (BER) pathway responsible for the repair of DNA lesions formed by reactive oxygen species (ROS). We report two cases of the MAP. In case 1, a 67-year-old woman presented with a personal history of colorectal and endometrial cancer and a family history of cancer syndromes that underwent multigene panel testing that revealed a germline homozygous (biallelic) pathogenic variant c.1187G>A (p.Gly396Asp) in the MUTYH gene. Subsequent sequencing analysis performed in offspring of the proband identified all three asymptomatic offspring as carriers of this pathogenic variant. In case 2, a 40-year-old woman with a strong family history of colorectal cancer (proband´s sister was a carrier of the pathogenic variant c.536A>G (p.Tyr179Cys) of the MUTYH gene) and renal cancer underwent sequencing analysis of the MUTYH gene. The pathogenic heterozygous (monoallelic) variant c.536A>G (p.Tyr179Cys) of the MUTYH gene was identified in proband. We found another pathogenic variant of the MUTYH gene - heterozygous (monoallelic) mutation c.1187G>A (p.Gly396Asp) in the genome of proband´s husband. Molecular analysis of their offspring revealed that they are compound heterozygotes for MUTYH pathogenic variants c.536A>G (p.Tyr179Cys)/ c.1187G>A (p.Gly396Asp). This paper shows the importance of the genetic testing of asymptomatic relatives of the proband to ensure an early surveillance and management of individuals positive for pathogenic variant(s) in the MUTYH gene.